Social protection as an enabler for economic development in the City of Johannesburg - Sidogi, Tshililo (My University, 2017)
The study explores the role of social protection in economic development, using the case of the Johannesburg. It argues that despite the city being the largest local economy in the continent; levels of poverty, unemployment and inequality remain high in part because the City of Johannesburg Metropolitan Council’s social and economic policies are not synergized accordingly. This is contrary to experiments in East Asian late industrialisation experiences, where social policy was designed as an enabler to economic development, and not as a residual policy aimed solely at creating safety nets.
A research report submitted to the Faculty of Management, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Sector Monitoring and Evaluation)
Keywords: Social policy; Welfare economics; Employee fringe benefits